A Legal Analysis of the Challenges in Proving Mens Rea in Corporate Criminal Cases Involving Environmental Crimes - Hairul Saleh Satrul (Rechtsvinding, 2026)
Corporations have become dominant economic actors in the modern era, yet their activities often trigger systemic environmental degradation. Proving the subjective element of means rea (guilty mind) in corporate entities remains a fundamental challenge in the Indonesian criminal justice system, which traditionally adhere to individual-based fault. Purpose of the Study: This research aims to analyze the juridical obstacles in proving corporate mens rea within environmental crimes and to evaluate the impact of regulatory shifts following the enactment of the Job Creation Law on evidentiary standards. Methods: This study employs a normative juridical method with statutory, conceptual, and case approaches. Results: The findings indicate that proving corporate mens rea is hindered by complex hierarchical structures, information asymmetry, and the "wilful blindness" of directors. Furthermore, redactorial changes in Article 88 of the Environmental Protection and Management Law (UU PPLH) via the Job Creation Law have created ambiguity regarding the principle of strict liability. However, Supreme Court Regulation (Perma) No. 13 of 2016 provides a procedural solution through functional indicators such as corporate profit and systematic failure to prevent violations. Conclusions: Effective environmental law enforcement requires a paradigm shift from psychological-human intent to organizational-corporate intent. The integration of environmental forensic audits and the adoption of aggregation theory are essential strategies to penetrate the corporate veil and achieve ecological justice.